2009
DOI: 10.1097/aog.0b013e3181a1f0e6
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Betamethasone Administration Alters Stress Physiology in Healthy Neonates

Abstract: A single course of antenatal betamethasone treatment induces a suppression of stress reactivity in healthy newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
4
41
2
1
Order By: Relevance
“…Resting cortisol levels and cortisol levels after this challenge were measured. While resting levels of cortisol were comparable between the infants with antenatal betamethasone treatment and controls, we found that the neonatal HPA axis was signifi cantly suppressed in infants with betamethasone treatment after the stimulus as these infants failed to adequately increase cortisol release (Schäffer et al, 2009;Fig. 6.1).…”
Section: Hpa Axis Functionality In Neonates After Intrauterine Betamementioning
confidence: 84%
“…Resting cortisol levels and cortisol levels after this challenge were measured. While resting levels of cortisol were comparable between the infants with antenatal betamethasone treatment and controls, we found that the neonatal HPA axis was signifi cantly suppressed in infants with betamethasone treatment after the stimulus as these infants failed to adequately increase cortisol release (Schäffer et al, 2009;Fig. 6.1).…”
Section: Hpa Axis Functionality In Neonates After Intrauterine Betamementioning
confidence: 84%
“…Saliva is an excellent medium to analyze such changes in the hypothalamus-pituitary-adrenal axis. The results of Schaffer et al [78] indicate that a single course of antenatal betamethasone treatment induces a suppression of stress reactivity in healthy newborns. Whether the observed effects transform into long-term consequences has to be established by follow-up studies.…”
Section: Saliva Assaysmentioning
confidence: 94%
“…This is based on studies in animals and humans showing changes in brain growth and neuronal development [15] in function of the hypothalamic-pituitary-adrenal axis [16] and in stress response in infants [17] after antenatal treatment with corticosteroids of the mother. As corticosteroid treatment not only affects lung surfactant but also numerous other aspects of lung structure and function, the possibility of long-term effects on the lung has been expressed [18] .…”
Section: Discussionmentioning
confidence: 99%